S100A8 calcium-binding expression in radicular and dentigerous cysts and in keratocystic odontogenic tumors - Iezzi Giovanna; Piattelli Adriano; Rubini Corrado; Goteri Gaia; Perrotti Vittoria; Artese Luciano; Fioroni Massimiliano; Carinci Francesco (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: Recently the term Keratocystic Odontogenic Tumor (KCOT) has been recommended for Odontogenic Keratocysts (OKC) to address the neoplastic nature of the lesion compared to radicular and dentigerous cysts. S100 are calcium-binding proteins involved in cell differentiation and inflammation, with a potential role in neoplastic transformation. Aim: The aim of this study was to evaluate whether S100A8 protein expression is different in KCOT compared to radicular cysts (RC) and dentigerous cysts (DC). Methods: A total of 84 consecutive odontogenic cysts, 34 RC, 25 DC, and 25 KCOT, were analyzed in this study. Results: Epithelial cells in KCOT cases were not immunoreactive for S100A8 except focally in cases associated with inflammation, while RC cases showed a variable positivity of all the epithelial layers from the basal to the superficial in 19/34 cases and DC cases showed a weak positivity of the intermediate and superficial layers in 7/25 cases. Conclusion: The lack of S100A8 protein expression seems to be observed more frequently in KCOT compared to RC and DC. This difference might be related to their neoplastic nature and a potential aggressive biological behavior for odontogenic cystic lesions.